PENGARUH PENGGUNAAN MEDIA FLANNEL BOARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK KELOMPOK B (USIA 5 – 6 TAHUN) DI TK CHIQA SMART PALEMBANG - Dika Sari; Darwin Effendi; Mardiana Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is titled “The Effect of Using Flannel Boards on Early Reading Skills in Group B Children Aged 5–6 Years at Chika Smart Kindergarten in Palembang.” In this study, the researcher used an experimental method with a one-group pretest-posttest design. The purpose of this study was to determine the effect of using flannel board media on early reading skills in Group B children aged 5–6 years at Chiqa Smart Kindergarten in Palembang. Sampling in this study was conducted using purposive sampling, as the sample was selected according to the needs of the study. The sample used in this study was class B2, consisting of 17 children, including 10 boys and 7 girls. Data collection was conducted through observation during the treatment to determine the results after the intervention. The research data was analyzed using SPSS 25 for Windows with a significance level of 0.05. From the results of the data analysis discussion, sig = 0.000 < 0.05 with t-count and t-table values of -21.459 > 1.753, it can be concluded that Ho is rejected and Ha is accepted, indicating a significant effect on early reading ability in group B children aged 5–6 years at Chiqa Smart Kindergarten in Palembang.